Modern visualization diagnostic methods of non-invasive breast carcinomas (review of literature) - D. A. Maksimov; A. M. Morozov; E. V. Penyaz'; V. V. Rogovenko; M. A. Belyak (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Breast carcinomas (BC) remain one of the most actual problems of modern oncology. According to statistics, the incidence of BC is steadily increasing, making it the most common cancer pathology among women. In this situation, the aspect of diagnosing BC at early, non-invasive stages, is certainly important, which still reduces mortality, increases the possibility of organ-preserving treatment, duration and quality of life of patients.The purpose of study. The purpose of study is to investigate and perform a comparative analysis of imaging techniques for the diagnosis of non-invasive breast carcinomas.Materials and methods. Modern Russian and foreign literature about the diagnosis of non-invasive breast carcinomas was analyzed. Publications not older than 7 years published in specialized medical editions were taken into account Results. Not only main, but also new, promising imaging modalities that are not currently part of routine practice were analyzed. The main imaging patterns in non-invasive breast carcinomas (DCIS, LCIS and Paget's breast cancer), feasibility and prognostic value of certain diagnostic methods in different nosologies of this disease were also discussed.Conclusion. The statistics provided explain the importance of breast carcinomas problem, as well as the relevance of its diagnosis at non-invasive stages. According to the authors, the issue of accurate diagnosis of breast cancer in situ is subject to further discussion and study, but we would like to note that when non-invasive breast carcinoma is suspected and doubtful imaging results are obtained, one should not limit oneself only to routine methods of imaging studies, but expand further diagnostic tactics until accurate results are obtained and a final diagnosis is made.